The Effect of Indirect Corrective Feedback in Reducing Error on Students’ Writing - Endah Anisa Rahma; Siti Sarah Fitriani (Proceedings of AICS - Social Sciences, 2016)
This experimental study aims to investigate the application of Indirect Corrective Feedback in reducing errors on students’ writing recount text. The subjects of the study were 60 tenth grade students of SMAN 1 Meulaboh chosen by random sampling. True experimental research was employed involving experimental group which was given Indirect Corrective Feedback and control group which was not given feedback. The instrument used was writing tests and the data were analysed by using Statistical Package for the Social Science (SPSS). This study focuses on giving Indirect Corrective Feedback on students’ writing recount in terms of grammatical features of the text. Therefore, there are nine error aspects mainly analysed, those are: verb, noun ending, spelling, word form, word order, pronoun, conjunction, missing and unnecessary word. The findings indicate that Indirect Corrective Feedback helps students to reduce errors in nine aspects. It is shown from the decrease of mean number of error in the post-test (12.17) which was lower than in the pre-test 27.07). It was also proven from errors performed in the pre-test as much as 388 and in the post-test as much as 250 from nine error categories. The results revealed that there was the reduction of error in the post-test. The finding confirmed that there is a significant difference between the results of post-test from both groups. It means that Indirect Corrective Feedback significantly improved the students’ writing achievement by the reduction of errors.